Awareness to health hazards and biosafety precautions among laboratory technicians working in tertiary-care center in Rajasthan, India - Himanshu Shekhar; Mukesh Patel; Cheeni Jain; Neha Garg; Ketan Mangukiya (Universiti Kebangsaan Malaysia, 2015)
Background: Awareness to health hazards and biosafety precautions among laboratory workers is an important aspect. Technicians handle blood or any biological sample may be at risk for accidental injury or exposure. They are exposed to a large pool of specimens from patients suffering from infections such as hepatitis B virus and human immunodeficiency virus. The lack of awareness regarding biosafety issues results in improper handling and/or dangerous laboratory practices during sample collection, processing, and discarding of specimens, potentially making laboratory technicians more exposed to pathogens. Objective: The aim of this study was to find out the level of awareness and biosafety measures taken by laboratory technicians during their routine work in a tertiary-care center. Material and Methods: A cross-sectional study was conducted at Geetanjali Medical College and Hospital (Central Lab), using a standardized and basic questionnaire, which enquired about awareness and precautions taken by technicians during laboratory work. All (N = 24) technicians enrolled in this study were from departments of pathology, biochemistry, microbiology, blood bank, and sample collection room. Results: Of 24 laboratory technicians, maximum (33.3%) technicians were from pathology department followed by biochemistry (25%) department. According to age, the youngest technician was of 24 years and the oldest was of 46 years. On the basis of their response regarding awareness, knowledge, and biosafety precaution questions, of 24 technicians, 8 (33.3%) were found aware of universal work precaution, 18 (75%) were found immunized with hepatitis B vaccine, and 18 (75%) were found to leave the laboratory without following proper hand wash rule after finishing duty. Conclusion: Knowledge of all the technicians is adequate but there is lack of awareness and practicality among them. There is need to develop standard operating procedures with biosafety training programs and self-hygienic procedures for laboratory workers.